Flow-batch analyzer for the chemiluminescence determination of catecholamines in pharmaceutical preparations - Grunhut, Marcos (2011)
A novel, simple, cheap, flexible, versatile, and highly sensitivity flow-batch analyzer (FBA) with chemiluminescence detection was developed for determination of dopamine, norepinephrine, and epinephrine in pharmaceutical preparations. The method was based on the inhibitory effect of the mentioned catecholamines on a luminol-potassium hexacyanoferrate (III) chemiluminescence system in alkaline medium. The optimization of the chemical variables affecting this chemiluminescence inhibition effect has been carried out using a Box-Behnken experimental design. The sample throughput was 28 h-1. The system allowed the automatic preparation of standard solutions and analytical process can be accomplished just by changing the operational parameters in FBA control software.